Analisis Semiotika Terhadap Prosesi Ngamuan Gunung Perak Pada Upacara Pernikahan Adat Dayak Maanyan Di Kabupaten Barito Timur - Rosi Patrisia; Patrisia Cuesdeyeni; Alifiah Nurachmana; Paul Diman; Misnawati Misnawati (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
This study aims to describe and analyze the symbolic forms, both connotative and denotative meanings contained in the Ngamuan Gunung Perak ceremony at the Dayak Maanyan traditional wedding using semiotic studies. The method used in this research is descriptive qualitative. The source of the data in this study was secondary data from video shows of Maanyan Dayak traditional wedding documentation. The instrument in this study is a documentation guide. Documentation guidelines are carried out by analyzing symbolic forms. The data analysis technique used in this study uses the semiotic study of Roland Barthes' theory of two-stage signification (Two orders of signification). The results of the research on the Ngamuan Gunung Perak procession that have been studied are sixteen symbolic forms of the existing denotative and connotative meanings. The symbolic forms are (1) the process of finding the complete silver mountain, (2) the process of finding and bringing the silver mountain to the bride and family, (3) the dance five times around the silver mountain by Wadian Bawo and Wadian Dadas, (4) Wadian calling the two the parents of the bride and groom, (5) lifting the silver mountain three times, (6) dancing nine times around the silver mountain by the bride and family, (7) Sangku, (8) Weah, (9) Pasike Tree, (10) Taringit , (11) Taringit's highest peak, (12) Silver money, (13) Banknotes, (14) Paper money at the end, (15) Junyung bowl, and (16) candles.